A fusion of charity and commercial investment principles to maximise social investment in South Africa - Nxumalo, Londa Selloane (Research of GSB, 2018)
South Africa faces a raft of social problems, the enormity of which make it impossible for the government to tackle alone. This has necessitated private sector involvement through socially responsible investments (SRI) and charity. Despite the growth of the SRI industry and years of charitable contributions, social investment into the high-impact areas that need it most remains far too low. This study seeks to understand what is holding back social investment, and how to address this. Using grounded theory methodology, the research finds that traditional SRI investors are inappropriate sources of funding and that charitable funds have largely been deployed inefficiently. The proposed solution is for more use to be made of charitable funders, with the disbursement process employing some commercial investment principles in order to facilitate the recycling of capital, resulting in the growth of social investment over time.